Development of a low grade lymphoma in the mastoid bone in a patient with atypical Cogan’s syndrome: A case report - Chris Kalogeropoulos; Dimitrios Karachalios; George Pentheroudakis; Aikaterini Tsikou-Papafrangou; Lydia Abou-Asabeh; Maria Argyropoulou; Alexandros Drosos; Nicholas Pavlidis (Journal of Advanced Research, 2015)
Cogan’s syndrome is a rare disorder characterized by ocular and audiovestibular manifestations in its typical form and caries a wide variety of atypical manifestations. It is considered as an autoimmune disease. We present the first case in the literature of a 67 year old woman with the development of low grade non-Hodgkin lymphoma (NHL) in the mastoid bone in a pre-existing history of atypical Cogan’s syndrome. The anatomical development of NHL was to a “target” organ of Cogan’s syndrome, which is the inner ear.